O chão onde as margaridas teimam em brotar: a experiência educativa de uma escola comunitária na Região Cacaueira da Bahia (1996-2012) - Cunha, Hundira Souza da (2017)
This research proposes to study the educational experience of the Margarida Alves Community Agricultural School (EACMA), in the municipality of Ilhéus-Bahia, between 1996 and 2012, when it functioned as an institution offering the last years of Elementary Education based on Alternance Pedagogy. During this period, the school was primarily aimed at the sons and daughters of peasants from the Bahian cacao region. With the objective of analyzing the experience of EACMA through the evaluation of the subjects involved on its institutional course, the study investigated the land issues and the education of the field in the cacao region of Bahia; The concept of "community" constructed by the peasants during the formation process of the school; And the senses elaborated by the subjects, movements and institutions involved with the institution about their role in the struggle for Field Education in the cacao region. To do so, I outlined the key question: "How do the subjects involved with EACMA evaluate the importance of their institutional course in the field of education in the Cocoa Region?" The categories "Community", "Field Education" Experience "and" Human Formation "as analysis references, establishing a dialogue with the empirical field and, through the case study, a search was made for a rapprochement with the field of research. The research used instruments such as semi-structured interviews and analysis of the political pedagogical project. The people heard in this study (women and youth, founders, students, teachers and field education activists in the region) highlighted "a way of making one's own" and "a collective experience" as the core of EACMA's educational experience, Importance of the institution for other actions in its life trajectories.